2017
DOI: 10.1097/md.0000000000007479
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of iodine uptake and perfusion parameters between dual-energy CT imaging and first-pass dual-input perfusion CT in lung cancer

Abstract: To investigate the potential relationship between perfusion parameters from first-pass dual-input perfusion computed tomography (DI-PCT) and iodine uptake levels estimated from dual-energy CT (DE-CT).The pre-experimental part of this study included a dynamic DE-CT protocol in 15 patients to evaluate peak arterial enhancement of lung cancer based on time-attenuation curves, and the scan time of DE-CT was determined. In the prospective part of the study, 28 lung cancer patients underwent whole-volume perfusion C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Our results showed that the NIC-A, NIC-V, NCT-A and NCT-V after treatment in the effective group were significantly lower than before treatment, and the NIC-V and NCT-V in the ineffective group were lower than those before treatment. After treatment, NIC-A, NIC-V, NCT-A, and NCT-A in esophageal cancer were all lower than those before treatment, indicating that CRT treatment led to reduced blood supply of EC, inhibited tumor cell proliferation, decreased tumor cells number, and thus reflected by the reduced tumor cells iodine intake, which is consistent with the previous study [ 18 ]. In addition, CMT drugs can exert toxic effects on cells and destroy vascular endothelial activity, induce necrosis of tumor lesions, mucosal congestion and edema, and inflammatory reactions, etc.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that the NIC-A, NIC-V, NCT-A and NCT-V after treatment in the effective group were significantly lower than before treatment, and the NIC-V and NCT-V in the ineffective group were lower than those before treatment. After treatment, NIC-A, NIC-V, NCT-A, and NCT-A in esophageal cancer were all lower than those before treatment, indicating that CRT treatment led to reduced blood supply of EC, inhibited tumor cell proliferation, decreased tumor cells number, and thus reflected by the reduced tumor cells iodine intake, which is consistent with the previous study [ 18 ]. In addition, CMT drugs can exert toxic effects on cells and destroy vascular endothelial activity, induce necrosis of tumor lesions, mucosal congestion and edema, and inflammatory reactions, etc.…”
Section: Discussionsupporting
confidence: 90%
“…Dual-energy CT (DECT) perfusion imaging can not only obtain the features found on conventional CT but also several quantitative and semiquantitative spectral parameters (water concentration, WC; iodine concentration, IC; the slope of spectral Hounsfield unit curve, λ HU ) and perfusion parameters (blood flow, BF; blood volume, BV; mean transit time, MTT; permeability surface, PS) of tumours through a one-stop DECT perfusion scan. This CT scan method has been widely used in the evaluation of extramediastinal tumours, such as neck lymphoma and lung cancer [13][14][15] . Although only a few studies have used IC or perfusion parameters alone to evaluate TETs [16][17][18][19] , no studies have used the two different kinds of parameters to identify the different pathological subtypes of TETs simultaneously.…”
mentioning
confidence: 99%
“…In the present study, the nIWR, n△HU and λHU values of metastatic lymph nodes were signi cantly greater than those of non-metastatic lymph nodes. Iodine concentration re ects the degree of contrast enhancement [23]. An increase of iodine content in metastatic lymph nodes could be due to the increased tumor-related angiogenesis, blood volume or vascular permeability within the metastatic lymph nodes [24].…”
Section: Discussionmentioning
confidence: 99%